Chapter Adult Educators and Recognition of Prior Learning in Portugal: Guidance and Validation Tasks and Activities - Guimarães, Paula (Studies on Adult Learning and Education, 2023)
Under the European Union lifelong learning guidelines, in the last two decades the Portuguese adult education policy has noted the emergence of new offers that have enabled the establishment of new occupations, tasks and activities for adult educators, such as those referring to guidance and validation within recognition of prior learning. Guidance and validation are developed on the basis of a wide range of tools (recommendations, guidelines, qualification frameworks, standards of competencies). This circumstance has allowed adult educators to become lifelong learning technicians as shown by the research conducted for the writing of this essay.